Electronic structure evolution induced by the charge redistribution during the construction of two-dimensional polymer networks from monomers to crystal frameworks. Issue 45 (14th November 2022) - Jing, Jian; Chen, Weikun; Huang, Zehua; Huang, Luyan; Liang, Xuefeng; He, Yan; Li, Huifang
Abstract : The electronic structure of COFs is dominated by the relative energy level between the frontier orbitals of building units, and the charge carrier mobility within the 2D structure is dominated by the charge transfer between core and linker units. Abstract : Two-dimensional covalent organic frameworks (COFs) are a new type of porous crystalline material constructed by the linkage of organic building units through covalent bonds to produce predetermined structures. Here, the electronic structure evolution induced by the charge redistribution during the construction of two-dimensional polymer networks (sp 2 c-COF-2 and COF-66) from building units to crystal frameworks is examined theoretically. The calculated results demonstrate that the electronic structure of the framework is controlled by the relative energy level between the frontier orbitals of organic building core and linker units as well as the charge transfer amount between them during the construction of the framework. Moreover, it is observed that a noncoplanar framework becomes more conjugated because the charge transfer amount between core and linker units becomes larger during the construction of 2D frameworks, which leads to a larger charge carrier mobility within the 2D structure of COFs. The charge carrier mobility along the z -direction of the COF crystal is dominated by the interface interaction between COF layers. Thereby, we believed reasonable design or selection of organic building units plays a key role in improving the electronic and optoelectronic properties of such 2D organic frameworks.